The liberal justice and human sexuality - Caviglia Marconi, Alessandro (2014)
The present paper explores the relationship among women, sexual minorities and the access to justice from the perspective of contemporary political liberalism of John Stuart Mill, Michael Walzer, John Rawls and Martha Nussbaum and the post-socialist prospect of Nancy Fraser. In this sense is detached from both the approach of the so-called third wave of feminism, because it rejects its centrality in the identity and the difference in biological basis, and the classical liberal approach thatdefines the terms of the justice without taking into account the voices of the subjects involved. At the same time, it explores the constitution of human sexuality from a hermeneutical perspective and seeks to establish the bases for sexual justice.